Concentrações plasmática e peritoneal da proteína de fase aguda ativina a em bezerros portadores ou não de hérnias umbilicais - Lima, Juliana Alves Nunes [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Activins are members of the transforming growth factor β (TGF-β) superfamily and can be synthesized by almost all cell types in the body and most tissues has the ability to be a source of activin A in circulation. Thus, the objectives of this study were to determine if plasma and peritoneal concentrations of activin A change in calves with or without umbilical hernia (UH) before and after surgery and in which compartment its increase would reflect better and faster inflammatory changes. Its role as an inflammatory biomarker in the abdominal cavity and the correlation between plasma and peritoneal concentrations, and establish reference intervals for the variable in each group. Twenty Holstein calves were used with (n = 10) or without HU (n = 10), calves with HU underwent herniorrhaphy. Whole blood and peritoneal fluid were collected from 20 animals for quantification of activin A by ELISA on days 0 (before surgery) 1, 3, 5, 7 and 15. Data were compared between the two groups. Plasma and peritoneal concentrations of activin A in the control group did not change over time, but in the experimental group there was an increase in the plasma concentration 15 days after herniorrhaphy compared to baseline. When comparing the groups, the plasma concentrations of activin A in the experimental group were decreased on day 3 and increased on the 15th day after surgery compared to the control group animals, while the peritoneal concentration had increased 5 days after herniorrhaphy repair in the experimental group compared to the control group
Keywords: Bezerro; Hernia; Bovino; Inflamação; Plasma - Densidade; Citocinas; Fator de crescimento transformador beta; Herniorrhaphy